Isolation and cryopreservation of Pseudopimelodus mangurus (Siluriformes) spermatogonial cells - Pessoa, Giselle Pessanha [UNESP]; López, Lucia Suárez [UNESP]; Rosero, Jenyffer Mairely; dos Santos, Silvio Carlos Alves; Yasui, George Shigueki; Senhorini, José Augusto [UNESP]; Monzani, Paulo Sérgio [UNESP] (Elsevier, 2024)
Spermatogonia cryopreservation can be a strategy for future conservation actions. The neotropical Siluriformes Pseudopimelodus mangurus was already classified as vulnerable on the Red List of Threatened Species. P. mangurus spermatogonial cells were isolated, assessed, and cryopreserved. Fragments of the testis were enzymatically dissociated, purified using Percoll density gradient, and submitted to differential plating. Fractionated cells were evaluated by microscopy, ddx4 (vasa) relative expression, and alkaline phosphatase activity. Cryopreservation was conducted using ethylene glycol, glycerol, dimethyl sulfoxide (DMSO), dimethylacetamide (DMA), and propanediol at 1 M, 1.5 M, and 2 M. Cell viability was evaluated and cell concentration was determined. Cell fractions from 20 % and 30 % Percoll gradient bands showed the highest concentrations of spermatogonia. The fraction mix showed 54 % purity and 93 % viability. After differential plating, 60 % purity and 92 % viability were obtained. Spermatogonial cells showed high alkaline phosphatase activity compared to spermatocytes and spermatids. The relative spermatogonial ddx4 expression from the Percoll density gradient was about twice as high as in samples from the testis and the differential plating. The increased ddx4 expression indicated the enrichment of spermatogonial cells by density gradient step and dead cells expressing ddx4 in differential plating, or ddx4 decreasing expression during cell culture. For this reason, cells from the Percoll gradient were chosen for cryopreservation. Propanediol at 1 M demonstrated the best condition for spermatogonial cell cryopreservation, presenting 98 % viability, while dimethylacetamide at 2 M represented the least favorable condition, with approximately 47 % viability. These findings are essential for P. mangurus spermatogonial cell cryopreservation, aiming to generate a spermatogonia cryobank for future conservation efforts.
Keywords: ddx4 expression; Differential plating; Endangered species; Gene bank; Percoll density gradient